Over-the-Top Cementing Technique in Cup-Cage Reconstructions - Lementowski, Peter (International Journal of Orthopedics and Rehabilitation, 2017)
Cup-cage constructs have been used for acetabular reconstruction in the setting of severe defects as well as pelvic discontinuity. This construct consists of a porous tantalum shell augmented with screws with an ilio-ischial cage that is placed over it. The superior flange of the cage is then affixed into the ilium with screws while the inferior flange is impacted into the ischial bone. A polyethylene cup is then cemented into the cage to complete the construct. The over-the-top cementing technique extends the extruded cement mantle from the polyethylene cup impaction over the superior flange creating a buttress construct to prevent screw back-out. In the setting of these complex cases this buttress effect can possibly improve the strength of the cup-cage construct.